Review of existing pest forecasting models and monitoring tools for key pests of maize, tomato, cowpea, sweet potato and yam - Gaitu, Christopher (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
As part of the objectives of the AICCRA project, there is to be the establishment of surveillance sites for key pests of the target commodities, namely maize, tomato, cowpea, sweet potato and yam in the project intervention districts. Extension officers who will oversee the surveillance sites will visit them weekly for observations and data collection. The pest information from the surveillance sites will then be packaged and sent to ESOKO for onward transmission to farmers in the AICCRA intervention districts. Before the establishment of the pest surveillance network there is the need to review any existing pest forecasting models for the key pests of the selected commodities. This is so as to identify any gaps in the existing pest forecasting models, benefit from previous experiences and also to inform the options for the way forward for the pest surveillance network. Currently the Centre for Agriculture and Biosciences International (CABI) as part of its Pest Risk Information Service (PRISE) sends pest information on key pests of selected commodities (Maize, Tomato) to farmers in selected districts in the country.